Antitumor Activity and Treatment-Related Toxicity Associated With Nivolumab Plus Ipilimumab in Advanced Malignancies: A Systematic Review and Meta-Analysis - Xu, Hang; Tan, Ping; Ai, Jianzhong; Zhang, Shiyu; Zheng, Xiaonan; Liao, Xinyang; Yang, Lu; Wei, Qiang (Frontiers in Pharmacology, 2019)
Combining immune checkpoint inhibitors has shown its efficacy compared to monotherapy in advanced malignancies. We conducted this meta-analysis to provide latest evidence on the objective response rate (ORR) and incidence of treatment-related high-grade adverse events (AEs) during nivolumab and ipilimumab combination treatment and further explore from different drug dose level. PubMed and the 2019 American Society of Clinical Oncology (ASCO) annual meeting abstracts were searched for qualified clinical trials up to June 2019. Of the 23 clinical trials (13 from publications and 11 from ASCO abstracts) included, 2114 and 2674 patients were eligible for efficacy and safety analysis, respectively. Pooled analysis suggested that the overall ORR was achieved in 34.5% (95%confidence interval [CI], 29.1%-40.4%) of patients. There was no significant difference between nivolumab 3 mg/kg plus ipilimumab 1 mg/kg every 3 weeks (N3I1-Q3W) and nivolumab 1 mg/kg plus ipilimumab 3 mg/kg every 3 weeks (N1I3-Q3W) arms in ORR (30.8% vs 41%; odds ratio [OR], 0.72; 95% CI, 0.39-1.30; P = 0.275). Grade 3-4 AEs related to combination therapy occurred in 39.9% (95%CI, 33.5%-46.7%) of patients; the most commonly reported grade 3-4 treatment-related AEs were diarrhea (5.28%), colitis (3.96%) and increased alanine aminotransferase (3.51%). Incidence of grade 3-4 AEs were significant lower in N3I1-Q3W arm than in N1I3-Q3W arm (31.3% vs 55.9%; OR 0.52; 95% CI, 0.32-0.87; P = 0.012). Treatment-related death was rare and occurred in 2.0% (95% CI, 1.5%-2.7%) of patients. Our comprehensive study provides more precise data on the incidence of treatment-related high-grade AEs and ORR among patients receiving nivolumab and ipilimumab combination regimens. Patients on the N3I1-Q3W arm had comparable ORR and significantly occurred less grade 3-4 AEs than patients on the N1I3-Q3W arm. Our finding is of great importance in assisting clinical trial design and clinical medication choice.